"Language, truth and logic" - "Ayer, A.J." (England, 1971)
Language, Truth and Logic is a 1936 book about meaning by the philosopher Alfred Jules Ayer, in which the author defines, explains, and argues for the verification principle of logical positivism, sometimes referred to as the criterion of significance or criterion of meaning. Ayer explains how the principle of verifiability may be applied to the problems of philosophy. Language, Truth and Logic brought some of the ideas of the Vienna Circle and the logical empiricists to the attention of the English-speaking world.
Keywords: Language-Philosophy.